Effect of flavonoids on skeletal muscle mass, strength and physical performance in middle-aged and older adults with or without Sarcopenia: A meta-analysis of randomized controlled trials - Li, Yuzhuo; Liu, Yun; Tan, Rongshao; Liu, Yan (Frontiers in Nutrition, 2022)
The role of flavonoids in regulating the synthesis and function of skeletal muscles is increasingly recognized. However, randomized controlled trials have yielded inconsistent results on the influence of flavonoids on human muscular parameters. Therefore, we performed a meta-analysis to evaluate the possible effects of flavonoids on sarcopenia-related parameters in middle-aged and elderly people. Eligible literature and randomized controlled trials reports have been extensively searched from PubMed, Cochrane Library, and EMBASE databases until April 2022. A total of 20 articles involving 796 participants were available for the meta-analysis. There were significant benefits for participants in appendicular muscle mass gain (SMD = 0.29; 95% CI: 0.07, 0.52; P = 0.01) and 6-minute walk distance (SMD = 0.37; 95% CI: 0.01, 0.73; P = 0.05). A subgroup analysis indicated that flavonoid significantly improves appendicular muscle mass (SMD = 0.50; 95% CI: 0.21, 0.80; P < 0.01) and Timed-Up and Go test (SMD = -0.47; 95% CI: -0.85, -0.09; P = 0.02) in Sarcopenia population. Our results provide insight into the effects of flavonoids on skeletal muscle mass and gait speed for those without exercise. However, there was no significant improvement in the subjects’ muscle strength. This study was registered on PROSPERO as CRD42022334383.